2021
DOI: 10.1021/acs.energyfuels.1c01687
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Kaolinite, Organic Matter, and Potassium Compounds at Elevated Temperatures during Pyrolysis of Caking Coal and Its Density-Separated Fractions

Abstract: Large coal agglomerates (cakes), which form in slow heating fixed-bed commercial gasifiers, result in low carbon efficiency and carbon loss in the ash assemblage. In an earlier study, laboratory-scale pyrolysis (600, 720, or 920 °C for 15 min) of a bituminous coal and its beneficiated fractions (>75 μm <1000 μm) was conducted to determine chemical reactions, which may inhibit caking propensity. It was found that the <1.5 g /cm 3 float achieved 70% caking compared to feed coal (18%) and its >1.9 g/ cm 3 sink (0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The ashes of these samples comprised mainly SiO 2 , Al 2 O 3 , CaO, SO 3 , Fe 2 O 3 , and MgO with minor percentages of TiO 2 , K 2 O, Na 2 O, and P 2 O 5 which are consistent with the ash composition of SA feed-coals to commercial gasifiers. 26 , 27 Mphahlele et al 28 found that higher concentrations of trace elements (Co, Zn, As, Rb, Sr, Zr, Ag, Cd, Ba, In, and Sn) and rare earth element (Y) are concentrated in the density-separated fractions of the FCR samples compared to the typical concentrations for SA Highveld ROM coals, as reported by Wagner and Hlatshwayo. 29 This could be associated with health and environmental issues during the storage of FCR samples in stockpiles and slime dams.…”
Section: Resultsmentioning
confidence: 78%
“…The ashes of these samples comprised mainly SiO 2 , Al 2 O 3 , CaO, SO 3 , Fe 2 O 3 , and MgO with minor percentages of TiO 2 , K 2 O, Na 2 O, and P 2 O 5 which are consistent with the ash composition of SA feed-coals to commercial gasifiers. 26 , 27 Mphahlele et al 28 found that higher concentrations of trace elements (Co, Zn, As, Rb, Sr, Zr, Ag, Cd, Ba, In, and Sn) and rare earth element (Y) are concentrated in the density-separated fractions of the FCR samples compared to the typical concentrations for SA Highveld ROM coals, as reported by Wagner and Hlatshwayo. 29 This could be associated with health and environmental issues during the storage of FCR samples in stockpiles and slime dams.…”
Section: Resultsmentioning
confidence: 78%
“…Other changes observed in the mineral composition include a decrease in diopside concentration from 4.4% to zero and an increase in illite from zero to 4.6%. Matjie et al (2021), Rautenbach et al (2020) and Rautenbach et al (2021) state that Al2O3•2SiO2 reacts with K + from the added potassium species to form K-feldspar in the chars and coal ashes upon pyrolysis and combustion of South African feed-coals. A lower pseudomullite proportion was also noted in the SA2 blend ash sample.…”
Section: Xrd Analysismentioning
confidence: 99%
“…An increase in the proportion of insoluble microcline in the SA2 blend ash samples prepared at 1050°C can be attributed to the reaction between potassium ions from the K₂CO₃ melt or K₂O reacting with metakaolinite, at elevated temperatures (Tables III and IV) (Rautenbach et al, 2021, Matjie et al, 2018. Matjie et al (2021) studied the reaction between metakaolinite and potassium cations to form synthetic K-feldspars by heating a blend of 10% K₂CO₃ and coal at 700°C and 1050°C in air. In addition, Collins et al (2018) used FACTSAGE™ modelling to predict microcline and kalsilite crystallization at temperatures between 1050°C and 1250°C from the melt of the SA2 blend.…”
Section: Coal Ash Mineralogymentioning
confidence: 99%
“…The synthetic potassium feldspar minerals, including microcline, form when potassium species react with metakaolinite at 600-700°C (Heller-Kallai, 1978;Heller-Kallai andLapides, 2003, Matjie, et al, 2021). Other potassium feldspars present in the coals begin to transform at temperatures of >1050°C (Matjie et al, 2021).…”
Section: Mineralogy Leached Ash Samples Mineralogymentioning
confidence: 99%